Ways to Terminate the Smart Contract: A Jurisprudential Study - Alomari, Sumaia Ali M. A (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: The research aims to shed light on the proposed solutions to terminate smart contracts through Blockchain technologies. To achieve this, the topic was addressed through two main aspects: the reality of smart contracts in the first aspect, and the proposed methods for terminating the smart contract in the second aspect. Methods: This study followed the descriptive approach, explaining the texts related to the description of smart contracts in terms of their nature and their relationship to Blockchain technology. It adopted a methodology of extrapolating jurisprudential, legal, and technical studies to address the research problem, along with an analytical approach to identify the main methods for terminating contracts within Sharia controls. Results: The study identified three methods to terminate smart contracts: deep learning technology, renegotiation terms technology, and termination through a cancellation contract. Conclusions: The researcher recommends further research into possible ways to terminate smart contracts while adhering to jurisprudential controls. She also calls for practical benefits from the experiences of countries that have adopted these contracts in their modern systems to identify and fill expected gaps.